2018
DOI: 10.1186/s12929-018-0464-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-8/CXCR1/2 signalling promotes tumor cell proliferation, invasion and vascular mimicry in glioblastoma

Abstract: BackgroundGlioblastoma multiforme (GBM) is one of the lethal malignant tumors of the central nervous system. Despite advances made in understanding this complex disease, little has been achieved in improving clinical efficacy towards it. Factors such as chemokines play important role in shaping the tumor microenvironment which in turn plays a significant role in deciding course of tumor progression. In this study, we investigated the role of chemokine IL-8 in glioblastoma progression with particular emphasis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 32 publications
3
59
0
1
Order By: Relevance
“…The authors showed that endothelial IL-8 increased GSCs invasiveness and growth [46,47]. Moreover, another report demonstrated that the IL-8-CXCR1/2 axis induces GBM proliferation, invasion, and vascular mimicry [48].…”
Section: Angiopoietin-2mentioning
confidence: 96%
“…The authors showed that endothelial IL-8 increased GSCs invasiveness and growth [46,47]. Moreover, another report demonstrated that the IL-8-CXCR1/2 axis induces GBM proliferation, invasion, and vascular mimicry [48].…”
Section: Angiopoietin-2mentioning
confidence: 96%
“…The sandwich invasion assay, a 3D spheroid invasion model, places a tumor neurosphere in between two layers of matrix then follows cells as they spread out from the central sphere (Figure 3b; Goertzen, Eymael, & Magalhaes, 2018;Markwell et al, 2019;Sharma, Singh, Siraj, & Saxena, 2018). Diverse ECMs can be incorporated into this assay, but most studies utilize either collagen I or Matrigel due to ease, rapid gelification, and commercial availability (Markwell et al, 2019;Naakka et al, 2019;Sharma et al, 2018). An acellular ECM layer is deposited into the bottom of a well then allowed to solidify (Goertzen et al, 2018;Markwell et al, 2019;Nath & Devi, 2016;Sharma et al, 2018).…”
Section: Sandwich Invasion Assaymentioning
confidence: 99%
“…Diverse ECMs can be incorporated into this assay, but most studies utilize either collagen I or Matrigel due to ease, rapid gelification, and commercial availability (Markwell et al, 2019;Naakka et al, 2019;Sharma et al, 2018). An acellular ECM layer is deposited into the bottom of a well then allowed to solidify (Goertzen et al, 2018;Markwell et al, 2019;Nath & Devi, 2016;Sharma et al, 2018). Next, neurospheres are suspended in the ECM mixture and placed atop the solidified ECM layer.…”
Section: Sandwich Invasion Assaymentioning
confidence: 99%
See 2 more Smart Citations